The Impact of Watching Films without Subtitles on Listening Skills of EFL Learners - Rangga Pradana, Muhamad Ihsan (BATARA DIDI : English Language Journal, 2023)
The purpose of the present work is to investigate the effects of English language films without subtitles on the listening comprehension of the mid-ability EFL learners. The research study that was conducted used a quasi-experimental design design and both quantitative and qualitative methods which included pre and post-test measures as well as focus group discussions. The subjects also included an experimental group which watched full films with no subtitle and a control group which equally watched the similar films with subtitles. These findings indicate that that the experimental group performed better than the control group in listening comprehension thus supporting the notion that elimination of subtitling aids in directing is attention and helps in the acquisition of inferential skills. The qualitative data also suggest that learners who watch the programs without subtitles paid more attention to the content listening to the dialogues while using contextual and visual context hence probably encouraging a more complex processing of the content. These findings indicate that although, with the help of subtitles spectators are initially comprehending the audio information, subsequent reliance on the subtitles harms the independent listening, which is essential for communication in real life. The study claims that there should be a gradual transition in the learner’s education process from using subtitles, so that the learners will be able to develop their own language learning capacity as well as prepare them for various communicative simulation.